An Experimental and Analysis Comparison of Solid Wood Bridle Joints with Various Fastener and Retrofit Methods - Sulendra, Ketut; Turu’allo, Gidion; Siregar, Atur (Engineering, Technology & Applied Science Research, 2025)
Teak (tectona grandis) is a material widely used for roof framing, known for its load-bearing capacity. Many buildings, including wooden ones, suffered significant damage after an earthquake due to failure of meeting technical requirements for seismic resistance. Therefore, it is necessary to strengthen the wooden roof trusses before a strong earthquake occurs. This study examines the structural behavior of L-type solid wood trusses under different fasteners, strengthening methods, and loading directions, and compares the experimental test with analysis methods. The test specimens consisted of teak L-joints with dimensions of 2 mm³ ×70 mm³ ×140 mm³ ×800 mm³ and a total of 32 pieces. Four types of fasteners were used: wooden plugs (4ø16 mm), bolts (4ø1/2"), nails (13ø3.76 mm), each with a length of 2.5", and screws (26ø3.50 mm) each with a length of 1.5". The retrofit materials were: L35.35.3 iron profile, C70.35.0.45 stainless steel, and 60.4 strip plate. The specimens were loaded in two directions: upright and sideways using a flexure tester with a maximum capacity of 150 kN and a maximum displacement stroke of 100 mm, which continued until peak load was reached, and then stopped after a load drop. The maximum load on the L-joint was found to be higher in the upright position than in the side-up position. The highest load capacities were achieved with the following fasteners: bolts, screws, nails, and wooden dowels, for both loading directions. Retrofitting with iron profile shows the greatest increase in load capacity for both loading directions. For right-up loading, retrofitting with strip plates is better than stainless steel, while for side-p loading, stainless steel retrofit is better than the strip plate. Failure modes were mainly shear cracks in the joint area originating from the bolt and pin holes. Failures were observed as breakage in wooden pins, and shear failure in nails and screws. The comparison of the maximum load capacity of the experimental test shows higher results compared to the results of the analysis calculation, with a ratio of about 1.20. The formula for calculating the load resistance of the joint, with a constant value of 73.11, in the literature review must be corrected to 70.80 for nail joints, 70.40 for bolt joints, and 62.10 for screw joints.